2016
DOI: 10.1113/jp272512
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in response to miRNA‐34a therapy in mouse models of cardiac disease: identification of sex‐, disease‐ and treatment‐regulated miRNAs

Abstract: MicroRNA (miRNA)-34a (miR-34a) is elevated in the diseased heart in mice and humans. Previous studies have shown that inhibiting miR-34a in male mice in settings of pathological cardiac hypertrophy or ischaemia protects the heart against progression to heart failure. Whether inhibition of miR-34a protects the female heart is unknown. Furthermore, the therapeutic potential of silencing miR-34a in settings of dilated cardiomyopathy (DCM) and atrial fibrillation (AF) has not been assessed previously. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
(96 reference statements)
2
34
2
1
Order By: Relevance
“…The study by Bernardo et al . () in this issue points out the need for a better understanding of microRNA expression differences in pathological tissues as correlated with sex and pathology. This may be especially important in the postmenopausal state.…”
Section: A Schematic Illustration Showing the Potential Mechanisms Fomentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Bernardo et al . () in this issue points out the need for a better understanding of microRNA expression differences in pathological tissues as correlated with sex and pathology. This may be especially important in the postmenopausal state.…”
Section: A Schematic Illustration Showing the Potential Mechanisms Fomentioning
confidence: 99%
“…Interestingly, a recent clinical study has suggested that circulating microRNAs are strongly impacted by age, sex and body mass index (Ameling et al 2015). The study by Bernardo et al (2016) in this issue points out the need for a better understanding of microRNA expression differences in pathological tissues as correlated with sex and pathology. This may be especially important in the postmenopausal state.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Endothelial microparticles are also known to carry and transfer microRNAs (miRNA or miR) to target tissues, including endothelial cells (Bernardo et al . ). miRNAs are ∼22 nt non‐coding RNAs involved in the regulation of a number of physiological and pathophysiological processes.…”
Section: Introductionmentioning
confidence: 97%
“…; Bernardo et al . ). For example, in vitro and in vivo studies have demonstrated that lower EMP expression of miR‐126 is associated with greater atherosclerotic plaque burden in mice and a higher incidence of atherosclerotic vascular disease in middle‐aged adults (Jansen et al .…”
Section: Introductionmentioning
confidence: 97%